Understanding factors affecting the purchase intentions of non-muslim in east Malaysia - Akang, Joy Samantha (2021)
The purpose of this study is to understand the underlying factors affecting the intentions of purchase of the non-Muslim in East Malaysia. Quantitative research method was chosen and data were collected through structured questionnaires. The sample data was tested by using SPSS software package. This study discovered that subjective norm and perceived behavioural control were found as a significant predictor to the conceptual model. Trust was tested as a moderator variable by using PROCESS macro and revealed that trust does significantly moderate the influence of attitude, subjective norm and perceived behavioural control of non-Muslim consumer on the intention to purchase halal products. Furthermore, the interaction effect between all variables was found to be significant. Future research should look into a particular halal product, certain age groups, and other constructs that may influence a significant moderating role. The study offers related organisations to invest in marketing strategies, human resource and technology development. This study is one of the very few attempts to understand the intentions of the non-Muslim consumers to purchase halal products specifically in Sabah.